Proyek Tata Kota dan Nostalgia Kolonial di Magelang - Ningrum, Siti Utami Dewi; Harnawan, Tedy (Balai Pelestarian Kebudayaan Wilayah X, 2023)
This paper investigates colonial narratives and legacies in Magelang in encouraging urban space reconstruction projects by local agencies; city government and history community. Cities and communities are important elements in urban planning for the formation of city identity and resilience in an everchanging urban landscape. Massive industrialization projects that demolish historical sites and erode local identity have initiated the establishment of a historical community to build collective memory and reclaim their lost local identity. The emergence of “Kota Toea Magelang” as a pioneering history community in excavating colonial history has influenced the city government in reproducing colonial symbols in public spaces. The local city government implemented an urban planning project with a taste of colonial nostalgia by launching the slogan “City of a Million Flowers” from a product of colonial knowledge to represent the modern city landscape.